The long run, market power and retail pricing - Adusei Jumah (Institute for Advanced Studies (IHS), 2000)
The paper uses the Johansen cointegration approach to analyse long-run pricing strategies of pork and chicken retailers in Austria. Long-run retail pricing strategy is found to be dependent on market share and price elasticity of demand for product. A combination of mark-up pricing strategy for pork and a competitive pricing strategy for chicken is considered by retailers to yield maximum profit. Long-run price adjustment reveals linkages to pricing strategy. The versatility of the Johansen cointegration technique as a tool capable of analysing both competitive and imperfect market situations is also revealed. The paper recommends meat policy to be product specific rather than holistic.
Keywords: C32; D43; L11; Q13; 330; market power; markup pricing; cointegration; long run; Einzelhandelspreispolitik; Lebensmittelhandel; Schweinepreis; Geflügel; Mark-up Pricing; Marktmacht; Kointegration; Schätzung; Österreich